Selecting a Quality Day Care for Young Children: A Cross- Sectional Survey of Parents in Karachi Pakistan - Bhamani, Shelina; Mughis, Waliyah; Fahim, Sara (JECCE, 2024)
Early childhood is a critical period for developmental milestones, yet in regions like Pakistan, limited access to quality daycare due to socio-economic constraints poses significant challenges. This study explores the impact of daycare quality on child development, focusing on the structural, systemic, and cultural factors that influence childcare in a low-income Pakistani context. This cross-sectional study involved 56 participants recruited from a tertiary care hospital early childhood parenting education club. Data were collected through online structured questionnaires assessing parental perceptions of daycare quality based on several criteria including proximity, safety, curriculum, and staff qualifications. Results highlight a significant discrepancy between parental expectations and the actual qualities of daycare services available.